Grape polyphenols supplementation for exercise-induced oxidative stress - Elejalde, E.; Villarán, C. M.; Alonso, R. M. (Journal of the International Society of Sports Nutrition, 2021)
Exercise induces free radicals` overproduction and therefore, an enhancement of oxidative stress, defined as an imbalance between the production of reactive species and the intrinsic antioxidant defense. Redox activity of reactive species plays an important and a positive role on exercise adaptation, but these species at very high concentrations have detrimental effects. As a result, the use of antioxidant supplements for reducing oxidative stress can be an effective health strategy to maintain an optimal antioxidant status. In this sense, grapes are an important source of natural antioxidants due to their high content in polyphenols. They have shown antioxidant potential benefits for the reduction of intense exercise effect in athletes of different sport disciplines. Consequently, it is plausible to hypothesize that a strategic supplementation with grape based products may be a good approach to mitigate the exercise induced oxidative stress. The goal of this review is to present the state of the art of supplementation effects with grape beverages and grape extracts on the oxidative stress markers in athletes. The data of polyphenolic dosages, participant characteristics and exercise protocols are reported.